Comparative Analysis of the Fecal Microbiota of Relict Gull (Larus relictus) in Mu Us Desert (Hao Tongcha Nur) and Bojiang Haizi in Inner Mongolia, China - Liu, Li; Du, Chao; Liu, Yunpeng; Gao, Li (Frontiers in Veterinary Science, 2022)
The gut microbiota contributes to host health by improving digestive efficiency and maintaining homeostasis. The relict gull (Larus relictus), a national first-class protected bird in China, is listed as vulnerable in the International Union for Conservation of Nature Red List. Here, 16S rRNA gene sequencing was performed to characterize and compare the community composition and diversity of the gut microbiota sampled from relict gulls in two breeding sites. In total, 418 operational taxonomic units were obtained and classified into 15 phyla and 228 genera. Alpha diversity analysis revealed no significant differences in community diversity among the two breeding sites. Beta diversity analyses showed that the microbial communities at the two sites were different. Six dominant phyla and fourteen dominant genera were identified. The most abundant bacterial genera had a significant relationship with the diet and living environment, and some bacterial genera were found to adapt to the plateau environment in which relict gulls live, which enables the relict gulls to use local resources effectively to accumulate energy. Simultaneously, a variety of highly abundant pathogenic bacteria was found, suggesting that these gulls may spread diseases among the local gull population. Certain measures should be taken to protect this species and to prevent the spread of diseases.